2015
DOI: 10.2528/pierm15082903
|View full text |Cite
|
Sign up to set email alerts
|

A Wideband Wide-Angle Ultra-Thin Metamaterial Microwave Absorber

Abstract: Abstract-A novel design of wideband, ultra-thin, wide-angle metamaterial microwave absorber has been presented. The unit cell of the proposed structure is designed by using parametric optimization in such a way that absorption frequencies come closer and give wideband response. For normal incidence, the simulated FWHM bandwidth of the proposed structure is 1.94 GHz, i.e., from 5.05 GHz to 6.99 GHz and −10 dB absorption bandwidth is 1.3 GHz from 5.27 GHz to 6.57 GHz. The proposed structure has been analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The wideband absorption of 8.30 GHz above 90% absorption was achieved using diagonally placed simple patches and dielectric substrate of thickness 3.2 mm . Subsequently, a metamaterial absorber of thickness λ 0 /32 (λ 0 is the free space wavelength) with 1.3 GHz absorption was obtained . Later, a structure with λ 0 /18 thickness and more compact than the earlier design was proposed with an absorption bandwidth of 3.75 GHz above 90% absorptivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wideband absorption of 8.30 GHz above 90% absorption was achieved using diagonally placed simple patches and dielectric substrate of thickness 3.2 mm . Subsequently, a metamaterial absorber of thickness λ 0 /32 (λ 0 is the free space wavelength) with 1.3 GHz absorption was obtained . Later, a structure with λ 0 /18 thickness and more compact than the earlier design was proposed with an absorption bandwidth of 3.75 GHz above 90% absorptivity.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Nowadays, wideband absorption with ultra-thin structure is essential in many metamaterial absorber applications. Thus, metamaterial absorber with multi-layer, 15,16 multiresonant, 17,18 and single layer [19][20][21][22][23][24][25][26] structures have been proposed for wideband absorption. Although, multilayer and multiresonant structures provide wideband absorption, they suffer from thickness and large size, respectively.…”
mentioning
confidence: 99%
“…al. [12]. It is found that the absorptivity for the proposed structure is less than 22.3% within operating frequency band of 4 GHz to 8 GHz.…”
Section: Introductionmentioning
confidence: 84%
“…This fact is addressed by the articles respectively [7][8][9][10][11]. In subsequent section, study and investigations are carried out on the structure proposed in [12], and it is shown that already reported structure is not a metamaterial absorber. al.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation